Calligraphy Business In Islamic Economic Review At An-Nida Calligraphy House Medan North Sumatra - Sartika Alpianti Manurung; Almita Wiguna (Yayasan Haiah Nusratul Islam, 2023)
Islamic calligraphy art is one of the works of art that has its own beauty characteristics so that it has a high selling value. At this time, many institutions or special places are deliberately built to foster a person's talent interest in calligraphy art and become a center for selling calligraphy tools or even calligraphy artwork itself, one of which is the An-Nida Calligraphy House. This research aims to find out how the development of the calligraphy business according to economics at An-Nida Calligraphy House since its inception until now. The method used in this research is a qualitative method, through literature review and interviews as data collection techniques, while the data analysis technique used is descriptive statistics. The results of this study indicate that the development of the calligraphy business at the Calligraphy House, which was built in 2017, has increased every year, and the variety of goods traded is increasingly diverse. This is evidenced by the increase in consumers and the progress of the construction of the Calligraphy House from year to year.